KUALITAS PELAYANAN PUBLIK DI KANTOR PERWAKILAN PEMERINTAH DAERAH KABUPATEN TOLITOLI DI KOTA PALU - Yuningsih, Rita (Katalogis, 2016)
The purpose of this study was to determine the perceptions on lodging service performance in The Representative Office of Tolitoli Local Government in Palu City. This study examines The Quality of the Public Service in The Representative Office of Tolitoli Local Government in Palu City from Tangibles, Reliability, Responsiveness, Assurance, and Empathy dimensions. The research type of this study was qualitative descriptive research, i.e. the problem-solving research type that illustrates or describes the research subjects and objects based on facts. The informants determined in this study were the employees of The Representative Office of Tolitoli Local Government in Palu City and the public service users of that Office. The data presented in this study were obtained directly from the research objects, those are interviews, observations, and documentations data. The results show that from (a) Tangibles and (b) Reliability dimensions, the public services are not in accordance with what is expected, whereas from (c) Responsiveness, (d) Assurance, and (e) Empathy dimensions, those can be considered good. Based on the results, the public service in The Representative Office of Tolitoli Local Government in Palu City is not optimal in giving satisfaction to the guests/visitors.